2005
DOI: 10.1186/1471-2148-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and geometry of canalization and developmental stability in Drosophila subobscura

Abstract: Background: Many properties of organisms show great robustness against genetic and environmental perturbations. The terms canalization and developmental stability were originally proposed to describe the ability of an organism to resist perturbations and to produce a predictable target phenotype regardless of random developmental noise. However, the extent to which canalization and developmental stability are controlled by the same set of genes and share underlying regulatory mechanisms is largely unresolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…A similar correspondence of patterns of shape integration for individual variation and FA has been found previously in the wings of Drosophila melanogaster [17], interspecific hybrids of two Drosophila species [40], tsetse flies [16], and bumble bees [41]. In contrast, two studies in Drosophila subobscura found considerable differences [22], [42]. Just as for insect wings, a range of different results was also found for mammals.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A similar correspondence of patterns of shape integration for individual variation and FA has been found previously in the wings of Drosophila melanogaster [17], interspecific hybrids of two Drosophila species [40], tsetse flies [16], and bumble bees [41]. In contrast, two studies in Drosophila subobscura found considerable differences [22], [42]. Just as for insect wings, a range of different results was also found for mammals.…”
Section: Discussionsupporting
confidence: 84%
“…Even when more complex genetic models are used, the covariance structure among individuals will depend on the particular mix of genotypes, and may not reflect the inherent patterns of canalization. This reasoning can explain the closer resemblance of the patterns of FA to those of environmental rather than of genetic variation that has been found in empirical studies that specifically examined this effect [3], [22], [46]. Likewise, phenotypic plasticity in response to environmental differences, such as different trophic morphs [19], may introduce heterogeneity of covariance patterns that are unrelated to other patterns of variation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other research supports the hypothesis that environmental canalization and developmental stability share underlying regulatory mechanisms, but environmental and genetic canalization do not [175]. Moreover, fluctuating asymmetry and phenodeviants in Drosophila bipectinata share a common buffering system [176].…”
Section: Adaptation Coadaptation and Heterozygositymentioning
confidence: 67%
“…Following Santos et al [58] the experimental flies were obtained from 54 crosses, which will be referred to as inbred (isogenic:Oj1×Oj1,Oj2×Oj2,...,Oj6×Oj6 with 18 crosses in total), or as outbred including both structural homokaryotypes (Oj1×Oj2,Oj2×Oj3,...,Oj6×Oj1 with 18 cyclically permuted reciprocal crosses in total) and heterokaryotypes (Oj1×Ok1,Oj2×Ok2,...,Oj6×Ok6; j ≠ k ; with 18 reciprocal crosses in total). Two developmental temperatures were used in the experiment to study potentially important effects of phenotypic plasticity: 18°C and 22°C.…”
Section: Experimental Settingsmentioning
confidence: 99%